Impaired performance of female APP/PS1 mice in the Morris water maze is coupled with increased A? accumulation and microglial activation. - LYNCH, MARINA ANNETTA; MINOGUE, AEDIN (My University, 2013)
Background: Alzheimer?s Disease is characterized by progressive neuronal loss and cognitive decline. Epidemiological studies suggest that the risk of AD is higher in women even when data are adjusted for age. Objective: We set out to compare changes in 9 month-old male and female mice which overexpress amyloid precursor protein (APP) with presenilin (PS1; APP/PS1 mice) and to evaluate whether any changes were coupled with deficits in spatial learning. Methods: APP/PS1 mice were assessed for their ability to learn in the Morris water maze and A? burden assessed by Congo Red and A? triple ultra-sensitive assay. Neuroinflammatory changes were examined in brain tissue along with expression of A?-generating and -degrading enzymes. Results: A deficit in reversal phase learning in the Morris water maze was observed in female mice and was paralleled by evidence of increased accumulation of A?, microglial activation and expression of IL-1?. Accumulation of A? was coupled with an increase in expression of BACE-1 and a decrease in insulin-degrading enzyme (IDE). Conclusion: The results indicate that the observed impairment in spatial memory in female APP/PS1 mice correlated with increased A? burden and the changes in A? may have occurred as a result of enhanced BACE-1 and decreased IDE expression.
PUBLISHED
Keywords: Alzheimer's disease